2016
DOI: 10.1111/apm.12486
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retroviruses in neurologic disease

Abstract: Endogenous retroviruses are pathogenic – in other species than the human. Disease associations for Human Endogenous RetroViruses (HERVs) are emerging, but so far an unequivocal pathogenetic cause‐effect relationship has not been established. A role for HERVs has been proposed in neurological and neuropsychiatric diseases as diverse as multiple sclerosis (MS) and schizophrenia (SCZ). Particularly for MS, many aspects of the activation and involvement of specific HERV families (HERV‐H/F and HERV‐W/MSRV) have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 127 publications
0
39
0
1
Order By: Relevance
“…Multiple sclerosis (MS) is another neurological disease in which ERVs have been strongly implicated. MSRV (multiple sclerosis-associated retrovirus), a subtype of ERV-W, as well as ERV-W1 and W2 and ERV-H/F have all been linked to MS (reviewed in Christensen, 2016). One study showed significantly elevated Env antigen in serum of MS patients relative to controls, while qPCR of ERV-W in mononuclear cells from blood (PBMC) showed association with MS relative to controls (Perron et al, 2012a).…”
Section: Ervs and Human Diseasementioning
confidence: 99%
“…Multiple sclerosis (MS) is another neurological disease in which ERVs have been strongly implicated. MSRV (multiple sclerosis-associated retrovirus), a subtype of ERV-W, as well as ERV-W1 and W2 and ERV-H/F have all been linked to MS (reviewed in Christensen, 2016). One study showed significantly elevated Env antigen in serum of MS patients relative to controls, while qPCR of ERV-W in mononuclear cells from blood (PBMC) showed association with MS relative to controls (Perron et al, 2012a).…”
Section: Ervs and Human Diseasementioning
confidence: 99%
“…A more heuristic hypothesis, however, would embrace the hypothesis that there may be several distinct upstream pathogenetic pathways that are driven by one or more basic mechanisms of biological aging, all of which lead to a common downstream pathway of beta amyloidosis, tauopathies and inflammation; if so, a nomenclature of “Dementias of the Alzheimer Type” (DAT) would be preferable (Martin, 2005b). Early precursors of DAT might conceivably range from nature-nature interactions and somatic mutations/epimutations that impact age-related aberrations in proteostasis (Yerbury et al, 2016) to the emergence of viral agents as a result of either immunosenescence (Shaw et al, 2010) or age-related alterations in the stability of chromatin leading to the expression of an endogenous retroviral agent (Christensen, 2016). Another argument in favor of pathogenetic heterogeneity is the common finding of mixtures of what have been considered to be distinct types of neuropathology, including frontotemporal dementia, Lewy Body dementia and multi- infarct dementia, especially for the case of older subjects (Rahimi and Kovacs, 2014).…”
Section: Arguments Pointing To the Pathogenetic Heterogeneity Of Amentioning
confidence: 99%
“…It has also been suggested that younger ERVs (i.e. more recently integrated ERVs) may play a role in human diseases including neurologic diseases (reviewed in [77]) and cancer [78]. ERVs may not only be directly disease causing, but may also modulate immunity, and evidence exists indicating a general role for ERVs in the regulation of interferon (gamma) responses [79].…”
Section: Introductionmentioning
confidence: 99%